APAKAH OPEC MERUPAKAN KARTEL?: PENDEKATAN KAUSALITAS GRANGER DALAM KERANGKA VECTOR AUTOREGRESSIVE - Andryan Setyadharma (KINERJA, 2006)
One would believe that The Organization of Petroleum Exporting Countries (OPEC) is certainly a cartel which curbs production in order to raise the price of its product as well as to share the market among its members. Did energy shock of the 1970’s engineered by an effective cartel of OPEC members acting to share the market by controlling output and influencing market prices? One would also expect OPEC's production to significantly affect the market price of oil as the organization is often accused of curbing production in order to raise prices. This paper tries to determine whether OPEC has the power of affecting the market price of oil and or vice versa. This study uses the Toda and Yamamoto (1995) procedure for testing for Granger non-causality in Vector Autoregressive (VAR) models that involves variables that are integrated of an arbitrary order and that are possibly cointegrated. The results indicate that there is no statistically significant causal relationship between real crude oil price and OPEC production in either direction for full sample period 1974 – 2005. Instead, we find that real crude oil price Granger cause OPEC production in 2 different sub samples period, but not in other direction. As overall we reject cartel hypothesis for OPEC as a whole.Keywords: OPEC, Granger Causality Test, VAR, Toda and Yamamoto